2021
DOI: 10.3389/fnut.2021.717918
|View full text |Cite
|
Sign up to set email alerts
|

Serum Albumin Before CRRT Was Associated With the 28- and 90-Day Mortality of Critically Ill Patients With Acute Kidney Injury and Treated With Continuous Renal Replacement Therapy

Abstract: Introduction: Although low serum albumin (ALB) may worsen acute kidney injury (AKI), additional study is needed to establish the connection between ALB and the prognosis of critically ill patients with AKI and treated with continuous renal replacement therapy (CRRT).Methods:A secondary analysis of a bi-center, retrospective, and observational study, such as critically ill patients with AKI and treated with CRRT from January 2009 to September 2016. The univariate analysis, multi-factor regression analysis, sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…In multivariate analysis, the HRs of initial hypoalbuminemia for 28-day and 90-day mortality were 0.63 (0.50–0.80) and 0.63 (0.51–0.78), respectively. The association between hypoalbuminemia and mortality was verified by Lv et al [ 6 ] in a retrospective review of 1132 AKI patients who required CRRT; their results showed HRs for 28-day mortality and 90-day mortality of 0.92 (0.89–0.95) and 0.92 (0.89–0.96), respectively.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…In multivariate analysis, the HRs of initial hypoalbuminemia for 28-day and 90-day mortality were 0.63 (0.50–0.80) and 0.63 (0.51–0.78), respectively. The association between hypoalbuminemia and mortality was verified by Lv et al [ 6 ] in a retrospective review of 1132 AKI patients who required CRRT; their results showed HRs for 28-day mortality and 90-day mortality of 0.92 (0.89–0.95) and 0.92 (0.89–0.96), respectively.…”
Section: Discussionmentioning
confidence: 78%
“…Similar trends were observed in previous studies. In Lv et al [ 6 ], the proportions of myocardial infarction and congestive heart failure were higher, while the mean SOFA score was lower, in the group with serum albumin ≥ 3 g/dL than in the group with serum albumin < 3 g/dL. Moon et al [ 8 ] showed that the proportion of patients with diabetes was higher, while the mean APACHE II score was lower, in the third tertile of albumin compared to the other tertiles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum albumin is related to cerebral ischemia ( Turhan et al, 2006 ), Alzheimer’s disease ( Skillbäck et al, 2017 ; Bode et al, 2018 ; Kim et al, 2020 ), Crohn’s disease ( Su et al, 2019 ), liver cirrhosis ( Chen et al, 2011 ; Oettl et al, 2013 ; Arroyo et al, 2014 ), chronic heart failure ( Jabbour et al, 2014 ), acute kidney injury ( Bang et al, 2018 ; Thongprayoon et al, 2018 ; Lv et al, 2021 ), chronic kidney disease ( Stoycheff et al, 2009 ; Zhang et al, 2015 ) and other diseases; however, the relationship between serum albumin and pulmonary function is unclear. Several studies have shown that in some acute respiratory diseases that lead to reduced pulmonary function, such as acute respiratory distress and acute lung, serum albumin increases capillary permeability, causing it to leak from blood vessels into tissue fluid or to escape into the alveolar space, resulting in reduced serum albumin levels ( Fanali et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hypoproteinemia, indeed, is very common in critically ill patients. Moreover, previous studies reported that hypoalbuminemia at the initiation of CRRT [ 9 ], as well as the dynamic changes of albumin during CRRT [ 10 ], are important risk factors for poor prognosis in AKI patients. Therefore, the formula of calculating the albumin corrected anion gap (ACAG) is described by Figge J et al in 1998 to correct the AG for fluctuations in the albumin concentration [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%